Measurement of Indoor Thoron Gas Concentrations Using a Radon-Thoron Discriminative Passive Type Monitor: Nationwide Survey in Japan - Sanada, Tetsuya (Int J Environ Res Public Health, 2021)
As part of a nationwide survey of thoron ((220)Rn) in Japan, the indoor (220)Rn gas concentrations in 940 dwellings were measured throughout one year, from 1993 to 1996, using a passive type (222)Rn-(220)Rn discriminative monitor. The monitor was placed in a bedroom or a living room in each house for four successive three-month periods. The mean annual indoor (220)Rn concentration was estimated from the four measurements in each house. The arithmetic mean, the median and the geometric mean for indoor (220)Rn concentrations in 899 dwellings were 20.1, 9.6 and 10.0 Bq m(−3), respectively. The (220)Rn concentrations exhibited a log-normal distribution. It was found that the (220)Rn concentrations were dependent on the nature of the materials used for wall construction and also on the distance of measurement from the wall. Significant seasonal variations in the (220)Rn concentration were not observed. It would seem that the nature of the wall material contributed to the increased indoor (220)Rn concentrations.